Left atrial function during exercise stress echocardiography as a sign of paroxysmal/persistent atrial fibrillation - Angela Zagatina; Quirino Ciampi; Jesus Vazquez Peteiro; Elena Kalinina; Irina Begidova; Ratnasari Padang; Alla Boshchenko; Elisa Merli; Matteo Lisi; Hugo Rodriguez-Zanella; Sergio Kobal; Gergely Agoston; et al. (Cardiovascular Ultrasound)
Abstract Objective Atrial cardiomyopathy is closely associated with atrial fibrillation (AF), and some patients exhibit no dysfunction at rest but demonstrate evident changes in left atrial (LA) function and LA volume during exercise. This study aimed to identify distinguishing signs during exercise stress echocardiography (ESE) among patients in sinus rhythm (SR), with and without history of paroxysmal/persistent AF (PAF). Methods A prospective cohort of 1055 patients in SR was enrolled across 12 centers. The main study cohort was divided into two groups: the modeling group (n = 513) and the verification group (n = 542). All patients underwent ESE, which included B-lines, LA volume index (LAVi), and LA strain of the reservoir phase (LASr). Results Age, resting and stress LAVi and LASr, and B-lines were identified as a combination of detectors for PAF in both groups. In the entire cohort, aside from resting and stress LAVi and LASr, additional parameters differentiating PAF and non-PAF patients were the presence of systemic hypertension, exercise E/e’ > 7, worse right ventricle (RV) contraction during exercise (∆ tricuspid annular plane systolic excursion < 5 mm), a lower left ventricular contractile reserve (< 1.6), and a reduced chronotropic reserve (heart rate reserve < 1.64). The composite score, summing all 9 items, yielded a score of > 4 as the best sensitivity (79%) and specificity (65%). Conclusion ESE can complement rest echocardiography in the identification of previous PAF in patients with SR through the evaluation of LA functional reservoir and volume reserve, LV chronotropic, diastolic, and systolic reserve, and RV contractile reserve. Graphical Abstract A scoring system predicting the probability of PAF. The score was computed using the cutoff values as in the illustration. The score >4 demonstrated a sensitivity of 79% and a specificity of 65% of PAF.